2015
DOI: 10.20473/j.djmkg.v48.i1.p43-47
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 1,25-dihydroxyvitamin D3 on MSX2 gene expression during tooth and alveolar bone development

Abstract: Background: 1,25-dihydroxyvitamin D3 has been proven to be able to control the formation and biomineralization of tissue through a regulatory gene. A previous research even showed that a cell responsible for the formation of the enamel, dentin and bone was the target of 1,25-dihydroxivitamin D3. Purpose: This research was aimed to determine the role of 1,25-dihydroxyvitamin D3 in vivo in the development of teeth and alveolar bone tissue by analyzing MSX2 gene expression as a gene marker responsible for the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In 1α-hydroxylase knockout mice 1,25(OH) 2 D had an anabolic role in dentin formation and dental alveolar bone development in mandibles, whereas PTH exerted an anabolic role predominantly in bone derived by endochondral ossification [36]. Moreover, it has been shown that 1,25(OH) 2 D, by an increased expression of MSX2 genes, may have a crucial role to regenerate all the mineralized tissues of the tooth, including enamel, dentin, cementum, and bone [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In 1α-hydroxylase knockout mice 1,25(OH) 2 D had an anabolic role in dentin formation and dental alveolar bone development in mandibles, whereas PTH exerted an anabolic role predominantly in bone derived by endochondral ossification [36]. Moreover, it has been shown that 1,25(OH) 2 D, by an increased expression of MSX2 genes, may have a crucial role to regenerate all the mineralized tissues of the tooth, including enamel, dentin, cementum, and bone [37,38].…”
Section: Discussionmentioning
confidence: 99%